Land snail genus Sarika Godwin-Austen, 1907 (Eupulmonata: Ariophantidae) from Cambodia, with description of three new species - Pholyotha, Arthit; Sutcharit, Chirasak; Thach, Phanara; Chhuoy, Samol; Ngor, Pen Bun; Panha, Somsak (European Journal of Taxonomy, 2020)
Taxonomic work on the land snail genus Sarika Godwin-Austen, 1907 in Cambodia is scarce. A total of three species were recognized from Cambodia prior to this study. However, their taxonomic descriptions were based mainly on shell morphology, with limited genital data. To address this knowledge gap, we opportunistically surveyed for land snails in Cambodia. Our inventory yielded four species of Sarika – one recognized species, Sarika bocourti (Morelet, 1875), from Battambang Province and three new species, Sarika khmeriana Pholyotha & Panha sp. nov., Sarika lactoconcha Pholyotha & Panha sp. nov. and Sarika nana Pholyotha & Panha sp. nov. from Kampot and Takeo Provinces in southern Cambodia. Our discovery involves the first species of Sarika to be described from Cambodia in more than a century highlights the extent to which the diversity of Cambodian land snails remains to be discovered. The status of two species, Sarika benoiti (Crosse & Fischer, 1863) and Sarika resplendens (Philippi, 1846), is at present ambiguous because no material identifiable as these species was found in recent extensive surveys. Although S. bocourti was recently collected from Cambodia, its taxonomic position remained unclear due to a lack of living specimens. Detailed descriptions and illustrations of living animals, shell morphology and reproductive anatomy are provided, and a map showing their distributions is given.